Formulation and evaluation of guapeva jam: nutritional properties, bioactive compounds, and volatile compounds during storage - MORAIS,Rômulo Alves (2022)
Abstract The guapeva (Pouteria cf. gardneriana Radlk.) is a Brazilian fruit that belongs to the Sapotaceae family and is considered a source of natural antioxidants and phenolic compounds; Thus, the objective of this work was to investigate the use of guapeva in the form of jam stored at different temperatures (25 °C and 35 °C) and to evaluate the degradation kinetics regarding the physicochemical parameters, bioactive compounds, and volatile profile, during the storage period of 150 days, in low-density polypropylene packaging’s. The stored jams were mainly influenced by the storage time variable, with significant reductions in titratable acidity, pH, color, vitamin C, carotenoids, ABTS●+, DPPH, and volatile profile. The temperatures studied were not able to significantly affect the shelf life determined for the jams; however, the best temperature for storage stability of the guapeva jams was 25 °C since the most significant degradation of the compounds occurs with the use of 35 °C. The correlation between time and temperature had no significant effect on carotenoid content.